ANALISIS TEORI HUMAN ERROR INFLANTION PERSPEKTIF Al-MAQRIZI DALAM MENYIKAPI GEJOLAK EKONOMI GLOBAL AKIBAT KONFLIK AMERIKA SRIKAT-IRAN - Khasanatul Maulidiyah; Mohammad Arif Syaifudin; Syifa'ul Jannahh; Sri Wigati (JURNAL EKONOMI PERJUANGAN, 2026)
Inflation poses a serious threat to global economic balance due to mismanagement and inappropriate economic policies. This study aims to analyze the relevance of Al-Maqrizi's ideas on human error inflation to the modern geopolitical conflict between the United States and Iran, which has led to rising world oil prices and global economic instability. The research method used is library research, analyzing various sources, such as books, journals, and scientific articles related to Al-Maqrizi's inflation theory and contemporary economic conditions. The results show that the geopolitical conflict between the United States and Iran has disrupted global energy distribution, increased world oil prices, and caused inflationary pressures in various countries. This phenomenon aligns with Al-Maqrizi's concept of human error inflation, which is inflation caused by human actions, political policies, and weak governance. The conflict also impacted international trade, global supply chains, and increased production and distribution costs in various countries. This study confirms that Al-Maqrizi's economic ideas remain relevant in understanding modern economic crises, particularly those related to the relationship between morality, political policy, and monetary stability. Inflation poses a serious threat to global economic balance due to mismanagement and inappropriate economic policies. This study aims to analyze the relevance of Al-Maqrizi's ideas on human error inflation to the modern geopolitical conflict between the United States and Iran, which has led to rising world oil prices and global economic instability. The research method used is library research, analyzing various sources, such as books, journals, and scientific articles related to Al-Maqrizi's inflation theory and contemporary economic conditions. The results show that the geopolitical conflict between the United States and Iran has disrupted global energy distribution, increased world oil prices, and caused inflationary pressures in various countries. This phenomenon aligns with Al-Maqrizi's concept of human error inflation, which is inflation caused by human actions, political policies, and weak governance. The conflict also impacted international trade, global supply chains, and increased production and distribution costs in various countries. This study confirms that Al-Maqrizi's economic ideas remain relevant in understanding modern economic crises, particularly those related to the relationship between morality, political policy, and monetary stability.